Pakistani Media and the Radicals: The Symbiotic Relationship and Its Impacts on Society and Free Speech - Muhammad Azam; Mudassar Hussain Shah; Saima Kausar (ASIAN Journal of International Peace & Security (AJIPS), 2024)
In Pakistan, radicalization constitutes a principal challenge confronting both the government and its citizenry. The interplay between media and radicalization phenomena in the country remains insufficiently explored. This research scrutinizes their reciprocal influences, particularly examining the extent to which radical organizations exert pressure on the media and the extent to which contemporary media facilitates the radicalization process. The overarching conclusion of this study indicates that the media has contributed to the proliferation of radicalism in Pakistan, at times deliberately and at times inadvertently. The recently more dynamic Pakistani media has consistently played a role in radicalizing individuals, groups, and organizations. Moreover, the media displays a tendency towards sympathy for radical elements. Radicals apply pressure on the media through various strategies. As evidenced in the survey conducted for this study, an overwhelming majority of Pakistani journalists perceive that the radicalization phenomenon has impacted the country’s media. A majority of respondents (57%) believe that the media has been suppressing information about radicalization phenomena. According to the survey, (69%) of respondents assert that radicalization has impaired the nation’s capacity to exercise free speech. Furthermore, (77%) of respondents acknowledge that radical groups exert pressure on the media.